2018
DOI: 10.1108/bij-07-2016-0112
|View full text |Cite
|
Sign up to set email alerts
|

Integrated SEM-FTOPSIS framework for modeling and prioritization of risk sources in medical device development process

Abstract: Purpose The purpose of this paper is to outline and prioritizes risk sources in medical device development (MDD) process using an integrated “structural equation modeling” (SEM) and fuzzy “technique for order performance by similarity to ideal solution (TOPSIS)” framework. Design/methodology/approach Risk sources which deter MDD process are explored through literature review. Initial structural model is proposed, factor loadings are determined by exploratory factor analysis and model fit is established by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Besides, there are insufficiencies in terms of policies and regulation to promote green procurement. In order to mitigate this issue, more mandatory requirements are needed to provide better sustainability (Kirkire et al, 2018).…”
Section: Green Procurement Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, there are insufficiencies in terms of policies and regulation to promote green procurement. In order to mitigate this issue, more mandatory requirements are needed to provide better sustainability (Kirkire et al, 2018).…”
Section: Green Procurement Challengesmentioning
confidence: 99%
“…The experts from industry and academics were consulted for the opinion. Delphi method is used by many researchers for survey as it maintains the anonymity of participants and considers individual opinions of the experts (Kirkire et al, 2018). To finalise and do pairwise ranking of the criteria, 50 experts were considered including supply chain managers, procurement managers and suppliers at Tier 1 and Tier 2 levels.…”
Section: Data Collectionmentioning
confidence: 99%
“…Structural equation based modelling and FTOPSIS framework (Kirkire et al, 2018) has been applied for modelling and ranking of barriers to MDD identified by Rane and Kirkire (2016).…”
Section: Resultsmentioning
confidence: 99%
“…Instead of using the two approaches separately, this article focusses on the use of integrated SEM and FTOPSIS methodology, which actually integrates quantitative and qualitative approaches. (Kirkire et al, 2018). Advantages of structural equation modelling.…”
Section: Structural Equation Modellingmentioning
confidence: 99%
“…A fuzzy TOPSIS methodology has been utilized for the prioritization of these disposition strategies for a cell manufacturing firm. Fuzzy TOPSIS methodology has been utilized by number of authors in the area of supply chain management (Agrawal et al, 2016c;Kumar and Singh, 2016;Singh et al, 2017;Kirkire et al, 2018).…”
Section: Introductionmentioning
confidence: 99%